Renal replacement therapies in the aftermath of the catastrophic Marmara earthquake - (:unkn) unknown (BLACKWELL PUBLISHING INC, 2002)
Background. Renal replacement therapy is of vital importance in the treatment of crush syndrome victims, who are frequently encountered after catastrophic earthquakes. The Marmara earthquake, which struck Northwestern Turkey in August 1999, was characterized by 477 victims who needed dialysis. Method. Within the first week of the disaster, questionnaires containing 63 clinical and laboratory variables were sent to 35 reference hospitals that treated the victims. Information considering the features of dialyses obtained through these questionnaires was submitted to analysis. Results. Overall, 639 casualties with renal complications were registered, 477 of whom (mean age 32.3 +/- 13.7 years, 269 male) needed dialysis. Among these, 452 were treated by a single dialysis modality (437 intermittent hemodialysis, 11 continuous renal replacement therapy and 4 peritoneal dialysis), while 25 victims needed more than one type of dialysis. In total, 5137 hemodialysis sessions were performed (mean 11.1 +/- 8.0 sessions per patient) and mean duration of hemodialysis support was 13.4 +/-9.0 days; this duration was shorter in the non-survivors (7.0 +/-8.7 vs. 10.0 +/- 9.8 days, P = 0.005). Thirty-four victims who underwent continuous renal replacement therapy had higher mortality rates (41.2 vs. 13.7%, P < 0.0001). Only eight victims were treated by peritoneal dialysis, four of whom also required hemodialysis or continuous renal replacement therapy. The mortality rate in the dialyzed victims was 17.2%, a significantly higher figure compared to the mortality rate of the non-dialyzed patients with renal problems (9.3%; P = 0.015). Conclusion. Substantial amounts of dialysis support may be necessary for treating the victims of mass disasters complicated with crush syndrome. Dialyzed patients are characterized by higher rates of morbidity and mortality.
Keywords: dialysis; Marmara earthquake; crush syndrome; acute renal failure; renal replacement therapy; emergency renal care; disaster relief; HANSHIN-AWAJI-EARTHQUAKE; CRUSH-SYNDROME; ARMENIAN EARTHQUAKE; TRAUMATIC RHABDOMYOLYSIS; FAILURE; DIALYSIS; VICTIMS; MANAGEMENT; DISASTERS